Civic Engagement and the Governance of Irish Suburbs - Peillon, Michel; Corcoran, Mary; Gray, Jane (Trinity College Dublin, 2006)
Civic Engagement and the Governance of Irish Suburbs addresses the policy implications of suburban growth in Ireland. The significant development of new suburbs, experienced since the early 1990s, is largely perceived as problematic, mainly because the social fabric in these places is considered to be weak and the 'sense of community' difficult to sustain. This paper is informed by a sociological study of one such 'new suburb', Ratoath Co Meath. The study explores the strength and texture of suburban civil society and examines the level of social capital in Ratoath through an exploration of local participation in social and public life. The authors discuss how a meaningful governance of the new suburban localities can be promoted and explore ways in which residents can participate in the decision-making processes affecting their local community. The policy options for the governance of these new suburbs are considered in this context, with a particular focus on ensuring that the participation processes for residents remain legitimate and inclusive.
Keywords: Social Policy; Irish suburbs; Ireland